Ensino de equivalência monetária por meio de um jogo de dominó adaptado - Jaeger Godoy, Maria Clara; Werner Alves, Hans; Xander, Priscila; dos Santos Carmo, João; de Souza, Silvia Regina (Acta Comportamentalia, 2015)